A sustainable shipping management framework in the marine environment: Institutional pressure, eco-design, and cross-functional perspectives - Wang, Lu; Yao, Jinge; Zhang, Haikuo; Pang, Qiwei; Fang, Mingjie (Frontiers in Marine Science, 2023)
The shipping industry plays a vital role in the world trading system and in maintaining the stability of global supply chains. However, we cannot ignore the damage it brings to the marine environment. With a focus on protecting the marine environment, the sustainable development of shipping companies has also drawn growing attention. This study examines the sustainable shipping management practice system and develops a comprehensive framework to evaluate the significance of influencing elements and prioritizes those factors. This paper adopts a fuzzy analytic hierarchy process method. It establishes a total of 11 sub-index systems from three aspects: the external policy pressure of shipping companies, the ecological design of shipping services, and the cross-functional green management within shipping companies. We used the fuzzy analytic hierarchy process (FAHP) to analyze data collected from 37 experts in the Chinese shipping industry. The findings show that external policy pressure is the most critical factor influencing sustainable shipping management, followed by eco-design and cross-functional green management. These factors have a big impact and provide management references for shipping company managers and policymakers. They also give the government a company perspective when creating pertinent regulations.